Penerapan Arsitektur Organik Pada Kawasan Agrowisata Kebun Teh Di Brebes, Jawa Tengah - muhammad arif hidayat; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Tea garden agro-tourism is an educational facility in Brebes, Central Java that accommodates natural tourism activities but teaches natural learning until the tea leaf picking process is educated and opened to all those who want to take a vacation and enjoy nature, in Agro tourism visitors are given the following knowledge: Learning to know nature further, practicing independence by understanding the community's interest in the culture of planting and caring for nature, especially tea plantations, can be generated by the existence of a forum to train and teach the community to care more about the surrounding environment. tours namely: Food court and caffetaria, tea galleries, libraries, guest houses, campgrounds, multipurpose halls, and. Recreational facilities: Services, shopping (tenants), ATM Center, and souvenir shops, landmarks or view towers, outbound zones, tea plantation zones / nurseries, home industries, green trees zones. Sports facilities: (Trampoline), pool, relaxing garden. Service Facilities: Mosque, laundry and house keeping. Supporting facilities: Mini trains and bicycles for tourist vehicles around the site. The tea garden agro-tourism located in Brebes, Central Java was taken into the form of the concept of implementation. The design of this development strives to provide a building function that accommodates teaching- learning activities with natural themes with an organic architecture approach. The concept of organic architecture is applied to an architectural philosophy that elevates harmony between human and natural dwelling.